Shaking table test of fabricated concrete shear wall structure and study on damage mechanism of strong earthquake. (September 2022) - Zhang, Zhong-Wei; Bai, Guo-Liang; Qin, Chao-Gang; Li, Jia-Rui; Liu, Han-Qing
Abstract: Prefabricated construction technology has the advantages of high quality, high efficiency, low cost, energy saving and environmental protection, and has developed rapidly in China in recent years. Based on the design and construction concept of "equivalent to cast-in-site", the seismic effect and strong earthquake damage mechanism of the overall structure considering boundary constraints are studied. In order to promote the application and development of high-assembly-rate concrete shear wall structures in high-intensity areas, a reduced-scale structural model of sleeve connection was designed and fabricated based on the Chinese seismic code. Through the multi-level strength-increasing shaking table simulation test, the dynamic characteristics, earthquake response, failure process and strong earthquake disaster mechanism of the model structure are comprehensively analyzed. The research results show that the prefabricated concrete shear wall structure can achieve the predetermined seismic fortification purpose according to the specified construction requirements. Secondly, Under the stepwise excitations of PGA 0.035–0.40 g, the flexural and shear failure of the coupling beam are the main failure mode, and the damage of the coupling beam with a small span-height ratio (1.33) is more serious. Furthermore, Under the stepwise excitations of PGA 0.62–0.90 g, the seismic capacity of the model structure is greatly reduced and there is a risk of collapse. The failure modes of the structure after a strong earthquake include four types: bending-shear composite failure of composite beams, horizontal interface penetration between composite beams and floor slabs, horizontal interface penetration between prefabricated walls and floor slabs, and vertical cracking at the junction surface of prefabricated walls and cast-in-site restraint elements. The latter three are unique forms of fabricated concrete shear wall structures. Finally, according to the whole process data of the test, the bottom shear force and top displacement of the model structure are calculated, and the hysteresis curve, skeleton curve and equivalent lateral stiffness are established. It is hoped that this study can provide a reference for the seismic design of high-rise fabricated concrete shear wall structures.